Parental and perinatal risk factors associated with onset of IBD: a systematic literature review and meta-analysis - Mallon, Kristian Paul; McBride, Ciara; O Morain, Colm Antoine; Doherty, Glen A.; Burns, Richeal (Frontiers in Gastroenterology, 2025)
IntroductionThere is accumulating evidence that certain perinatal and prenatal factors may contribute to the onset of IBD, however evidence on some risk factors is inconsistent. The present study seeks to extend current knowledge on these risk factors and provide a comprehensive overview of which factors are associated with IBD onset and their direction of effect.MethodsA Systematic review and meta-analysis of case-control, cohort studies and randomised controlled trials (RCTs) investigating the association between parental and perinatal factors and onset of IBD was conducted. Studies were included if they reported details on patients with a diagnosis of IBD (including Crohn’s Disease [CD] and/or Ulcerative Colitis [UC]), defined and measured according to endoscopic, radiological, and histopathological findings, confirmed by a gastroenterologist or physician. Computerised bibliographic searches of Ovid MEDLINE, Web of Science, and the Cochrane Library were conducted from 01/01/2002 to the 01/01/2022. Where possible, summaries of the effects of perinatal and prenatal variables for each study were provided by calculating risk estimates using the DerSimonian and Laird random effects model. Levels of heterogeneity were evaluated using the I² statistic. Data were analysed using Stata version 17. Study protocol details are published on the International prospective register of systematic reviews (PROSPERO), registration number: CRD42022290798.ResultsFifteen eligible studies were identified, encompassing 9 case-control and 6 cohort studies, with no RCTs identified. A total of 6,507 patients with IBD were described in these studies (1,819 UC; 3,908 CD; 754 IBD; 4 IBD-unclassified patients). Three predictors of IBD risk were identified. Any poor maternal health or disease in mother during pregnancy (Pooled RR 1.78, 95% CI 1.24-2.31), maternal IBD (Pooled RR 4.59, 95% CI 1.68-7.50), and familial history (Pooled RR 2.87, 95% CI 1.80-3.93), were associated with an increased risk of overall IBD.DiscussionThis systematic review and meta-analysis suggests parental and perinatal factors may have a role in the onset of IBD. These findings highlight the importance of early-life exposures for later IBD development and indicate a requirement for further research in this area.Systematic Review RegistrationPROSPERO, identifier (CRD42022290798).